Analisis Kompetensi Kewirausahaan Industri Kecil Suku Cadang di Kota Padang - Prima Fithri; Amanda Febria Sari (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2012)
As economic development and current technology, there tends to SMEs have been reversed there is some effort to close down due to lack of existing orders in the business. Therefore, the government made efforts to assist existing SMEs to be able to survive in the face of global crisis is happening right now. These efforts may include providing small loans and may include training services in accordance with its business. One of the materials provided in the training is about entrepreneurship so that SMEs are expected to compete with similar companies. The low ability entrepreneur pointed out as one of the reasons SMEs are not able to compete with large companies, such as SI (Small Industry) Spare Parts in the city of Padang. The failure to penetrate IK Parts of competition to supply spare parts in the PT. Semen Padang because of its low ability entrepreneur is owned by SI. With no indicator of entrepreneur ability, there are some problems for governments about policies that will be taken for judge the SI. Therefore, the entrepreneur ability should be decided to helps government in decisions making of policies, so that SI can be competing with larger companies. The method that been used in this study is the Quality Function Deployment (QFD) and the recommendations for policies that can be used by the government by using SWOT analysis. QFD is used to identify consumer needs and its association with the characteristic techniques provided by the government, so that the final results are the critical competencies that should be developed first. The linkage between the needs of consumers with technical characteristics reflected in the House of Quality (HOQ). While the results of the SWOT analysis are four types of strategies which can be used later by using the strategy outlined in the strategy implementation architecture for 10 years. This research resulted in 25 indicators of entrepreneurial competencies that include Human Resources (HR), financial, and research and development which consist of eight aspects. The resulting formulation of strategies using SWOT analysis generates SO Strategies (5 strategies), WO Strategies (7 strategies), ST Strategies (7 strategies), and WT Strategies (5 strategies). The design of the implementation of the strategy is planned for 10 years which is reflected in the architecture of the strategy and its implementation strategies.Keywords: small industries, indicators, competences, entrepreneur, strategies